PLASMODIUM DOMINAN DALAM NYAMUK ANOPHELES BETINA (Anopheles spp.) PADA BEBERAPA TEMPAT DI DISTRIK MANOKWARI BARAT - Rina A. Mogea (Jurnal Natural, 2018)
Malaria contagious by mosquito Anopheles Betina bringing protozoa parasite in its body (Plasmodium). Plasmodium there are four specieses that is Plasmodium vivax, Plasmodium ovale, Plasmodium malariae and Plasmodium falciparum, but often becomes pathogen that is Plasmodium vivax and Plasmodium falciparum. As for intention of this research is to identify Plasmodium which is dominant at female Anopheles mosquito (Anopheles spp.) and knows distribution pattern of female Anopheles mosquito (Anopheles spp.) in some places in Districts Manokwari Barat. Based on research result done to four locations that is area Amban, Wosi, Sanggeng and Kota is found [by] 1024 mosquito tails. From the amounts only 115 mosquito tails was mosquito Anopheles Betina while the other is mosquito Anopheles male, mosquito Culex and Aedes. Mosquito Anopheles Betina found consisted of 4 species that is Anopheles bancrofti, Anopheles kochi, Anopheles farauti and Anopheles koliensis. Mosquito Anopheles Betina which is dissected, obtained 2 the Plasmodium species in mosquito spit gland is Plasmodium vivax and Plasmodium falciparum, and from calculation by index dominant can be told that both types of this very dominant Plasmodium in Districts Manokwari Barat because its the dominant index > 5%.